Influence of Budget Availability, Value Engineering (VE), Life Cycle Cost Analysis (LCCA), and Green Building Understanding on Green Building Implementation in School Buildings in DKI Jakarta - Siriyah Nindry Noviardini; Agus Suroso (Green Publisher Indonesia, 2026)
The application of the green building concept in school buildings in DKI Jakarta is one of the strategic steps in supporting sustainable development. The concept aims to improve energy efficiency, reduce environmental impact, and create a healthy learning environment. However, the level of implementation still faces various challenges influenced by a number of factors. This study aims to analyze the influence of budget availability, Value Engineering (VE), Life Cycle Cost Analysis (LCCA), and understanding of green building concepts on the level of application of green building concepts in school buildings in DKI Jakarta. This study uses a quantitative approach with a survey method. Data was obtained through questionnaires distributed to related parties, such as school managers, consultants, and contractors involved in the construction and renovation of school buildings. Data analysis was carried out using multiple regression techniques to test the influence of each independent variable on the dependent variable. The results of the study show that the availability of budget, VE, LCCA, and understanding of green building concepts significantly affect the level of application of green building concepts in school buildings. Budget availability is a major factor influencing implementation decisions, while VE and LCCA contribute to efficient and sustainable decision-making. On the other hand, the level of understanding of the concept of green building also plays an important role in determining the extent to which this concept can be applied optimally. This research provides recommendations to local governments, school managers, and related parties to increase budget allocation.